خصائص الصيغ المفردة في القرآن الكريم - حمد، فوزي إبراهيم صالح (جامعة سرت - نقابة أعضاء هيئة التدريس, 2020)
يحاول الباحث في هذه الدراسة الموجزة إلقاء الضوء على الخصائص البلاغية للمفردة القرآنية، حيث لوحظ أن جل دراسات المهتمين بإعجاز القرآن الكريم وبلاغته تركزت حول نظمه وتراكيبه. وشاهد ذلك ما قرره شيخ البلاغيين الإمام عبد القاهر الجرجاني (ت471ه) في مستهل مصنفه البلاغي الفريد (دلائل الإعجاز) قال: "ليس لنا إذا نحن تكلمنا في البلاغة والفصاحة؛ مع معاني الكلم المفردة شغل، ولا هي منا بسبيل، وإنما نعمد إلى الأحكام التي تحدث بالتأليف والتركيب". (دلائل الإعجاز، 1992، ص 72). ويمكن أن يحمل كلامه على المنهجية التي اختارها لنفسه، بحيث تنصب دراسته على نظم القرآن فقط، وليس إنكارا لمكانة المفردة القرآنية وإعجازها البلاغي. وإن وجدت دراسات اهتمت بفصاحة اللفظ المفرد، لكنها في أغلبها دراسات على المستوى النظري، ولم تول المفردة القرآنية حقها من بيان ما تتضمنه من بلاغة وإعجاز. مثل كتاب (سر الفصاحة) لابن سنان الخفاجي (ت466ه) وكتاب (المثل السائر) لابن الأثير (ت637ه). وهذا البحث محاولة متواضعة لبيان ما تضمنته المفردة القرآنية من خصائص بلاغية إعجازية، انطلاقا من اعتقادنا الراسخ بأن القرآن المجيد معجز في ألفاظه المفردة، كإعجازه في نظمه وتراكيبه المبهرة. In this brief study, the researcher tries to shed light on the rhetorical characteristics of the Qur’anical singular, where it was observed that most studies of those interested in the miracle of the Holy Quran and its rhetoric focused on its systems and structures. And witnessed that decided by the Sheikh of the rhetoric Imam Abd al-Qaher al-Jarjani (d. 471 AH) at the beginning of his unique rhetorical work (Evidence of Miracle), he said: “We have not spoken of eloquence and eloquence with the single meanings of speech, and it is not one of us in a way, but rather we refer to the provisions that Speak with composition and composition". His words can be carried on the methodology he chose for himself, so that his studies focus only on the systems of the Qur’an, and not a denial of the prestige of the Quranic term and its rhetorical miracle. And if there are studies concerned with the eloquence of the singular word, but they are mostly studies at the theoretical level, and the Qur’anic term has not given its right to explain the rhetoric and miracles it contains. Such as the book (The Secret of eloquence) by Ibn Sinan al-Khafaji (d. 466 AH) and the book (The Parable of Walking) by Ibn Al-Atheer (d. 637 AH). This research is a modest attempt to show the rhetoric contained in the Qur’anic miraculous properties, based on our firm belief that the glorious Qur’an is miraculous in its singular terms, such as its miracle in its impressive systems and structures.
Keywords: القرآن الكريم -- البلاغة القرآنية -- التفاسير اللغوية -- النحو العربي